Implementation of RFID to Improve The Security of TNI-AD Personnel in The Ammunition Disposal Area - Hendarto Sihotang; Reski Resdiawan (International Research & Development for Human Beings (IRDH), 2025)
Ammunition storage areas are critical sites that pose significant security and safety risks for the Indonesian Army (TNI AD). Effective security measures are essential to ensure safe operations in these high-risk zones. This study explores the potential of Radio Frequency Identification (RFID) technology to enhance security and personnel monitoring in TNI AD ammunition disposal operations. The objective is to assess how RFID can improve real-time tracking, access control, and personnel safety in hazardous areas. Using a combination of system design analysis and implementation challenges, the research examines the benefits of RFID for ensuring authorized access and reducing risks such as unauthorized entry, accidents, and human losses. Findings suggest that RFID technology significantly enhances security by enabling continuous tracking of personnel and monitoring of their movements, thus improving the overall efficiency and safety of ammunition disposal operations. This study recommends the integration of RFID technology into military operations as a means to bolster personnel security and support TNI AD's broader mission of safeguarding national security.